2000
DOI: 10.1021/bi000387i
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Vanadate Induce Tyrosine Phosphorylation of Phosphoinositide-Dependent Kinase 1 (PDK1)

Abstract: Phosphoinositide-dependent kinase (PDK1) regulates a number of pathways involved in responses to stress and in growth factor signaling; however, little is known concerning the mechanisms governing the activity of PDK1. In this report, we find that oxidative stress (H(2)O(2)) and vanadate induce tyrosine phosphorylation of PDK1. These effects of H(2)O(2) and vanadate were found in 293T cells and CH310T1/2 cells expressing exogenous PDK1 and in A20 lymphoma cells expressing endogenous PDK1. Exogenously expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 55 publications
10
75
0
Order By: Relevance
“…SGK shares a regulatory pathway with Akt. Like Akt, SGK can be activated by PI3K [120][121][122] even though it lacks a PH domain. Secondly, both Akt and SGK are directly phosphorylated and activated by PDK1.…”
Section: Pi3k/akt Signaling and The Bcl-2 Family Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…SGK shares a regulatory pathway with Akt. Like Akt, SGK can be activated by PI3K [120][121][122] even though it lacks a PH domain. Secondly, both Akt and SGK are directly phosphorylated and activated by PDK1.…”
Section: Pi3k/akt Signaling and The Bcl-2 Family Of Proteinsmentioning
confidence: 99%
“…Secondly, both Akt and SGK are directly phosphorylated and activated by PDK1. 119,122 Interestingly, SGK and Akt phosphorylate different residues of FKHR-L1 and synergistically inactivate B-Raf.…”
Section: Pi3k/akt Signaling and The Bcl-2 Family Of Proteinsmentioning
confidence: 99%
“…To test whether SGK plays a role in B-Raf regulation, we examined B-Raf kinase activity in the presence or absence of SGK. HA-B-Raf was transfected in HEK293 cells with SGK-S422D, which is a constitutively active SGK mutant containing the activation phosphorylation site Ser 422 substituted by an aspartic residue (42). HA-SGK-S422D was used because wild-type SGK has low activity in the absence of serum stimulation.…”
Section: Inhibition Of B-raf By Sgk-mentioning
confidence: 99%
“…Several groups have reported that SGK could also be activated by the PI3K pathway (40,41). PDK1 is likely to directly phosphorylate and enhance SGK activity (41,42). However, physiological targets of SGK are largely unknown.…”
mentioning
confidence: 99%
“…Oxidative stress is intrinsically associated with a state of increased turnover of biomolecules induced by elevated rates of reactive oxygen species. However, extensive studies have recently demonstrated that other proteins also increase their activity upon oxidative stress in a significant manner, for example c-Jun NH 2 -terminal kinase (49), p70-S6 kinase (50), Akt/PKB (51), glucose-6-phosphate dehydrogenase (52), PDK1 (53), and SGK (54), among many other examples. Interestingly, the last two proteins are related to the mineralocorticoid biological response.…”
Section: Discussionmentioning
confidence: 99%